THE COMBINATION OF TASK-BASED LEARNING (TBL) APPROACH AND AUDIO VISUAL AIDS TO IMPROVE STUDENTS’ ACADEMIC WRITING SKILLS - Anna Stasya Prima Sari; Jontra Jusat Pangaribuan (JURNAL LINER (Language Intelligence and Educational Research), 2018)
This research was primarily conducted to prove that the combination of Task-Based Learning (TBL) approach and audio visual aids could improve the students’ academic writing skills and to describe the students’ responses after learning academic writing skill through the combination of TBL approach and audio visual aids. This research is Classroom Action Research (CAR), which was performed in two cycles (cycle 1 and cycle 2). Each cycle consisted of four meetings. The subject of the research is the fourth semester students of English Language Education Study Program of Catholic University of Saint Thomas North Sumatera in the Academic Year of 2017/2018. There are 21 students as the subject of the research. The analysis of quantitative data showed that the students’ mean score increased continuously from 66,05 in the pretest, 78,62 in the posttest of cycle 1 to 88,81 in the posttest of cycle 2. The analysis of qualitative data showed that the learning teaching processes of academic writing skill, particularly writing the English essays through the combination of TBL approach and audio visual aids ran very well. The combination of TBL approach and audio visual aids could also increase the students’ interest, motivation and involvement in the classroom activities. It is advisable that teachers or lecturers of English language should try combining TBL approach and audio visual aids to improve their students’ academic writing skills